Young, Brave and Selfless: Grit Characters' in Ta'awun Behavior of Young Muhammadiyah Volunteers - Sovi Septania; Khairani Khairani (Jurnal Sains Psikologi, 2020)
This research purpose is to empirically analyze how grit is connected with ta’awun behavior. This research used the grounded theory approach. Data collection methods through in-depth interviews, observation, and focus group discussions. Data integration utilized the triangulation method through three main stages, consist of open, axial, and selective coding. Respondents consisted of four young volunteers with specific criteria such as act as active volunteers at Muhammadiyah Disaster Management Centre (MDMC), students of Muhammadiyah Lampung University, and had practical experience in the disaster area. The results showed that there were five main themes in the behavior of Muhammadiyah's young volunteer ta'awun: (1) attention to others; (2) helping others; (3) considerate others; (4) positive achievement; dan (5) positive consequences. Grit character in the behavior of young Muhammadiyah volunteers involves as a rover to success system in aligning young volunteers to give added value to the utmost usefulness in the process of assisting survivors. Further explanation in understanding its various connection was discussedKata Kunci: young volunteer; muhammadiyah; ta’awun; grit